10 years of advancing diversity within the Mycological Society of America - Mycological Society of America Diversity, Equity and Inclusion Committee (IMA Fungus)
Like most Science, Technology, Engineering, and Mathematics (STEM) fields, mycology has been dominated by white male scientists, while representation of marginalised groups (e.g., women, persons from different racial and ethnic groups, persons with disabilities, and members of the LGBTQ+ community) remains low. Here, we discuss diversity, equity, and inclusion in mycology and report on the last decade’s efforts to improve diversity in this field. We highlight changes and initiatives implemented by the Mycological Society of America and assess their success. We conclude by making recommendations for the next steps required to achieve non-discrimination and balanced representation in mycology.